2020
DOI: 10.1111/1440-1703.12118
|View full text |Cite
|
Sign up to set email alerts
|

Daily inundation induced seasonal variation in the vertical distribution of soil water salinity in an estuarine mangrove forest under a tropical monsoon climate

Abstract: Previously, we revealed opposing patterns of the vertical distribution of soil water salinity between the dry and rainy seasons in an estuarine mangrove forest under a tropical monsoon climate. This study clarifies the causes of such seasonal variation in soil water salinity distribution. We investigated the salinity of inundating water, and diurnal changes in soil water salinity and water table levels. Freshwater inundated the study plot in the rainy season, while saline water inundated it in the dry season. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…The variation in inundation frequency and period affects the soil salinity distribution in the mangrove forest. At the same study site as that investigated in our study, Komiyama et al [28] reported that the horizontal distribution of soil-water salinity differed remarkably between the dry and rainy seasons. During the dry season, the salinity levels were high on the river edge occupied by Sonneratia and Avicennia trees and became low towards the inland areas dominated by the Rhizophora and Xylocarpus trees.…”
Section: Mangrove Forest Structure and Biomasssupporting
confidence: 52%
See 4 more Smart Citations
“…The variation in inundation frequency and period affects the soil salinity distribution in the mangrove forest. At the same study site as that investigated in our study, Komiyama et al [28] reported that the horizontal distribution of soil-water salinity differed remarkably between the dry and rainy seasons. During the dry season, the salinity levels were high on the river edge occupied by Sonneratia and Avicennia trees and became low towards the inland areas dominated by the Rhizophora and Xylocarpus trees.…”
Section: Mangrove Forest Structure and Biomasssupporting
confidence: 52%
“…Thus, the soil-water salinity showed both spatial and seasonal fluctuations [28] corresponding to the species distribution in our study plot. Supporting the distribution of the Avicennia and Sonneratia trees in a wide range of soil salinities, Parida and Jha [38] reviewed that the two genera had three mechanisms of salt adaptation, namely, salt secretion, salt exclusion, and salt accumulation.…”
Section: Mangrove Forest Structure and Biomassmentioning
confidence: 65%
See 3 more Smart Citations